Dziecko w ramach wojny. Przypadek Donbasu - Wojciech Siegień (Problemy Wczesnej Edukacji)
The paper presents the results of ethnographic research on the mechanism of war framing combined with an analysis of the representation of children. Based on the analysis of materials from the Russian media (the case of crucifixion of a boy in Slavyansk) and ethnographic interviews with teachers in Kramatorsk, the author asks questions about the mechanisms of constructing the ontologies of child subjects by institutions of power in the conditions of war and the differentiation of grief after them. The conducted analysis, based mainly on the theses of Judith Butler, shows the differences in the construction of child subjects on both sides of the conflict. The author also points to the similarities in the treatment of children’s bodies, understood universally as the projection surface of affects,especially those related to patriotism.